Strategi Pencegahan Japanese Encephalitis (JE) Melalui Vaksinasi pada Anak Usia Dini di Wilayah Endemis - Naimah, Siti; Jennifa, Jennifa (Dharma: Jurnal Pengabdian Masyarakat, 2025)
Japanese Encephalitis (JE) is an infectious disease of the central nervous system caused by the Japanese Encephalitis Virus (JEV), JEV is the main cause of viral encephalitis in Asia. This virus is transmitted by mosquitoes and is zoonotic. The purpose of this activity is to prevent the occurrence of JE in residents of Donohajo Village, Yogyakarta. The method used in this community service is in the form of direct vaccination to the Donoharjo community with the criteria of being between 9 month to < 15 years old, having no history of seizures and not having had a fever in the last 1 week. The implementation of the Japanese Encephalitis Vaccination activity was carried out for 3 days, namely from 7 to 9 October 2024 at the Donoharjo Village Hall. The parties involved in this activity were lecturers and students of Stikes Guna Bangsa Yogyakarta. The number of children who received the JE vaccine in this activity was 342 people